High-altitude meteors and meteoroid fragmentation observed at the Jicamarca Radio Observatory - Gao, B. (2014)
Modern high-power, large-aperture (HPLA) radars have been used in a variety of investigations including the investigation of meteoroid fragmentation. The identification of fragmentation has been based on a detailed interpretation, based on radio science, of head- and trail-echo properties. We now extend the discussion of fragmenting meteoroids to include apparent high-altitude (130–180 km) meteors observed at the Jicamarca Radio Observatory (JRO). While there have been a few reports of high-altitude meteors observed both optically and with radar, the meteor radar community has remained sceptical, with suspicions of antenna side-lobe contamination being the most commonly raised objection. We report results from two sets of meteor observations carried out at JRO in 2010 April. Our findings include meteoroid fragmentation results that are similar to those from the Arecibo VHF radar. These findings lead to the conclusions that fragmentation is not only observed at the JRO but that k⊥B scattering adds an interesting additional radio science dimension to the issue. We also report on apparent high-altitude meteor events that, if ultimately confirmed, offer insight into sputtering as a source of the meteor ionization, and perhaps indicate the unique importance of magnetic field geometry in these head-echo observations. Also, new, apparently high-altitude transient events, likely related to the meteoroid flux, have been identified. In presenting these results, we note our careful calibration of the JRO radar, utilizing satellite returns in order to largely, if not totally, exclude side-lobe contamination and other possible error sources, as reported in our companion paper.